Path Following With Finite-Time Convergence for Unmanned Surface Vehicle - Huang, Yanwei; Lai, Guozhen; Lin, Feng; Shi, Xiaocheng; Li, Dongfang (IEEE journal of oceanic engineering, 2025)
A path-following control scheme is proposed using finite-time convergence line-of-sight (FCL) to achieve rapid convergence of position errors for an unmanned surface vehicle (USV). FCL combines classical line-of-sight (LOS) guidance with finite-time stability theory to ensure that the position of the USV converges to the reference path within a predetermined finite time. Specifically, a USV model is developed to analyze target tracking. Moreover, a novel cross-tracking error function is designed with hyperbolic characteristics for FCL through an analysis of the relationship between convergence speed and cross-tracking error function. Further, the path-following system stability with FCL and finite-time controllers is analyzed to indicate the smaller value of the upper bound of the system convergence time by comparisons. Finally, simulations and experiments are performed to verify that FCL has a faster convergence speed than the LOS with error sign function (LS) and the linear cross-tracking error function (LLCF), and a wider algorithm parameter tuning range compared to LS.